2023
DOI: 10.14814/phy2.15737
|View full text |Cite
|
Sign up to set email alerts
|

Altered collagen I and premature pulmonary embryonic differentiation in patients with OI type II

Abstract: Pulmonary hypoplasia and respiratory failure are primary causes of death in patients with osteogenesis imperfecta (OI) type II. OI is a genetic skeletal disorder caused by pathogenic variants in genes encoding collagen type I. It is still unknown if the collagen defect also affects lung development and structure, causing lung hypoplasia in OI type II. The aim of this study was to investigate the intrinsic characteristics of OI embryonic lung parenchyma and to determine whether altered collagen type I may compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Unlike previous studies where it was not possible to differentiate between a restrictive and an obstructive problem using FOT (36), our technique was able to assess the resistance, reactance, and the resonant frequency during both inspiration and expiration, giving insights in the respiratory function. Our findings provide support for the presence of obstructive lung disease in OI patients, as observed in four patients through standard PFTs and nearly all patients using FOT (16,32). These results are consistent with the recent Danish study that emphasized obstructive disease as a significant contributor to hospitalization, medical utilization, and mortality in patients with OI (29).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike previous studies where it was not possible to differentiate between a restrictive and an obstructive problem using FOT (36), our technique was able to assess the resistance, reactance, and the resonant frequency during both inspiration and expiration, giving insights in the respiratory function. Our findings provide support for the presence of obstructive lung disease in OI patients, as observed in four patients through standard PFTs and nearly all patients using FOT (16,32). These results are consistent with the recent Danish study that emphasized obstructive disease as a significant contributor to hospitalization, medical utilization, and mortality in patients with OI (29).…”
Section: Resultssupporting
confidence: 91%
“…However, the Danish study linked respiratory-related deaths to chronic obstructive pulmonary disease (29). Our recent study on OI type II fetuses revealed intrinsic lung alterations, suggesting similar changes in other OI types (32). Our understanding of the mechanisms behind respiratory complications in OI remains limited.…”
Section: Resultsmentioning
confidence: 99%